MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
sanket sit Grade: 11
        

2207_7579_scan0001.jpg

7 years ago

Answers : (1)

Saineel Sanjay Prabhudessai
32 Points
										

For x<0, f(x)= 1+x3. Therefore g(f(x))= g(1+x3)= (1+x3-1)1/3= x.


for x> or =0, f(x)=x2-1. therefore g(f(x))= g(x2-1)=( x2-1+1)1/2= x.


threfore g(f(x))=x for all x belonging to (-infinity,infinity).


 


Thanks,


Saineel.

7 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details
Get extra Rs. 1,272 off
USE CODE: Neerajwin
Get extra Rs. 136 off
USE CODE: Neerajwin

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details